Identification of the human cerebral cortical hemodynamic response to passive whole-body movements using near-infrared spectroscopy - Zhao, Yue; Wei, Yue; Wang, Yixuan; So, Richard H. Y.; Chan, Chetwyn C. H.; Cheung, Raymond T. F.; Wilkins, Arnold (Frontiers in Neurology, 2023)
The human vestibular system is crucial for motion perception, balance control, and various higher cognitive functions. Exploring how the cerebral cortex responds to vestibular signals is not only valuable for a better understanding of how the vestibular system participates in cognitive and motor functions but also clinically significant in diagnosing central vestibular disorders. Near-infrared spectroscopy (NIRS) provides a portable and non-invasive brain imaging technology to monitor cortical hemodynamics under physical motion. Objective This study aimed to investigate the cerebral cortical response to naturalistic vestibular stimulation induced by real physical motion and to validate the vestibular cerebral cortex previously identified using alternative vestibular stimulation. Approach Functional NIRS data were collected from 12 right-handed subjects when they were sitting in a motion platform that generated three types of whole-body passive translational motion (circular, lateral, and fore-and-aft). Main results The study found that different cortical regions were activated by the three types of motion. The cortical response was more widespread under circular motion in two dimensions compared to lateral and fore-and-aft motions in one dimensions. Overall, the identified regions were consistent with the cortical areas found to be activated in previous brain imaging studies. Significance The results provide new evidence of brain selectivity to different types of motion and validate previous findings on the vestibular cerebral cortex.